Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak dalam Melakukan Pembayaran Pajak Bumi dan Bangunan Perdesaan (Studi Wajib Pajak PBB-P2 di Kabupaten Kutai Kartanegara) - M. Hayyun Alfarezi; Muhammad Iqbal (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to examine and analyze the factors that influence taxpayer compliance in paying rural and urban land and building taxes in Kutai Kartanegara Regency. This study uses quantitative methods and primary data in the form of questionnaires with Likert scale measurements. The results showed that tax knowledge has no significant effect on compliance of land and building taxpayers, with a p-value of 0.309 (more than 0.05) and a t-statistic of 0.499 (less than 1.66), so H1 is not proven. Tax sanctions have a positive and significant effect on land and building taxpayer compliance, with a p-value of 0.024 (less than 0.05) and a t-statistic of 1.980 (more than 1.66), so H2 is proven. Taxpayer awareness has a positive and significant effect on land and building taxpayer compliance, with a p-value of 0.000 (less than 0.05) and a t-statistic of 3.377 (more than 1.66), so H3 is proven.